The flames of hope - Sutherland, Tui, 1978- (Sutherland, Tui, 1978- Wings of fire, 2022)
Luna returns to Pantala with her team of dragons, fighting her way into the abyss hiding the poisonous roots infecting the land. Uncovering a long-buried secret, Luna realizes that she'll need the dragons, her friends, and her enemies to unite if they are to save their world from destruction.